Challenges of solid waste management in Malaysia - Behzad, Nadi; Ahmad, Rodzi; Saeid, Pirasteh; Elmira, Shamshiry; Mokhtar, Mazlin (International Congress of Chemistry and Environment, 2011)
Malaysia is faced with challenges with respect to the solid waste management sector because of the increase of population and tourism, economic growth for sustainable development and inadequate waste legislation enforcement, infrastructure and public attitude among residents. This paper gives an approach of the solid waste management in Malaysia with the aim of presenting the state of waste management practices and problems with regards to environmental, economic and other ramifications.